2006
DOI: 10.1103/physreva.73.013820
|View full text |Cite
|
Sign up to set email alerts
|

Optical storage of high-density information beyond the diffraction limit: A quantum study

Abstract: We propose an optical read-out scheme allowing a demonstration of principle of information extraction below the diffraction limit. This technique, which could lead to improvement in data read-out density onto optical discs, is independent from the wavelength and numerical aperture of the reading apparatus, and involves a multi-pixel array detector. Furthermore, we show how to use non classical light in order to perform bit discrimination beyond the quantum noise limit.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This property becomes important as the NA is increased, and has been studied for several years now. Its most common intended applications reside in the areas of optical storage [10,11], microscopy and scanning optical microscopy [12][13][14], photonic force microscopy [15], lithography [16], laser micro-fabrication, particle guiding or trapping [17,18], and single molecule imaging [10,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…This property becomes important as the NA is increased, and has been studied for several years now. Its most common intended applications reside in the areas of optical storage [10,11], microscopy and scanning optical microscopy [12][13][14], photonic force microscopy [15], lithography [16], laser micro-fabrication, particle guiding or trapping [17,18], and single molecule imaging [10,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…phase coding scheme can be extended to implement a multi-pixel array detector. Delaubert et al [28] has performed a quantum study of multi-pixel array detection and shown that it is possible to perform multipixel transverse spatial phase encoding. Possible implementation of a multi-pixel scheme would require the incorporation of multiple interferometers and the use of multi-squeezed beams or a multi-mode OPO system [29].…”
Section: Discussionmentioning
confidence: 99%
“…[9]). Increasing the number of correlated modes is of particular importance, for instance in the case of optical read-out technologies [12] and super-resolution techniques [13]. In this context, generating continuous-variable polarizationentangled light [1,2,3], which exhibits three or four mode correlations, is a first step towards increasing the phase space dimension.…”
Section: Introductionmentioning
confidence: 99%